2021
DOI: 10.5603/demj.a2021.0009
|View full text |Cite
|
Sign up to set email alerts
|

Profile of practices and knowledge on stroke among Polish emergency medical service staff

Abstract: BACKGROUND:Stroke is a leading cause of disability and death in both developed and developing countries. While hemorrhagic stroke often necessitates immediate neurosurgical intervention, ischemic stroke is treated with reperfusion therapies such as thrombolysis with intravenous recombinant tissue plasminogen activator (IV rtPA) and early endovascular thrombectomy for broad vessel occlusions. OBJECTIVES:Early diagnoses, accurate emergency medical services (EMS) dispatch, rapid EMS transfer, and stroke team acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…For HSM-1 ( Stroke is a medical emergency only within 4.5 h of stroke onset ), 70% of our participants were unaware of thrombolysis above 4.5 h. Intravenous thrombolysis can also be considered for acute stroke onset more than 4.5 h up to 9 h or in wake-up stroke or stroke of uncertain onset assisted by CT/MR perfusion (significant penumbra mismatch) or MRI (DWI-FLAIR mismatch) ( Academy of Medicine of Malaysia, 2021 ). Our finding is similar to that reported previously, especially regarding the treatment of extended hours of stroke; most participants were unaware of stroke treatment beyond 4.5 h ( Blek & Szarpak, 2021 ). Thus, potentially treatable stroke patients could be missed due to poor knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For HSM-1 ( Stroke is a medical emergency only within 4.5 h of stroke onset ), 70% of our participants were unaware of thrombolysis above 4.5 h. Intravenous thrombolysis can also be considered for acute stroke onset more than 4.5 h up to 9 h or in wake-up stroke or stroke of uncertain onset assisted by CT/MR perfusion (significant penumbra mismatch) or MRI (DWI-FLAIR mismatch) ( Academy of Medicine of Malaysia, 2021 ). Our finding is similar to that reported previously, especially regarding the treatment of extended hours of stroke; most participants were unaware of stroke treatment beyond 4.5 h ( Blek & Szarpak, 2021 ). Thus, potentially treatable stroke patients could be missed due to poor knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that HCPs who saw stroke patients in daily practice, especially doctors and those working with specialists, had better overall knowledge of stroke, showing that experience and proper guidance are the determinant factors of stroke knowledge. Similarly, previous studies reported that being a physician ( Rababah, Al-Hammouri & AlNsour, 2021 ), working in a stroke-related speciality ( Mellon et al, 2015 ), and seeing more stroke cases ( Blek & Szarpak, 2021 ), are significantly associated with higher stroke knowledge. Furthermore, training, skill, and expertise in acute stroke care were significantly associated with higher thrombolysis rates ( Paul et al, 2015 ).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations